Serum Hemoglobin Level in Preeclampsia - Akhtar, Selina; Any, Umme Hafsa; Fahmi, Sonia (Journal of Current and Advance Medical Research, 2021)
Background: Pre-eclampsia is the major cause of maternal and fetal mortality and morbidity. It affects approximately 5-8% of pregnant women. Objectives: The study was undertaken to find an association between Hemoglobin and preeclampsia. Methodology: This cross-sectional study was carried out in the Department of Physiology at Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka, Bangladesh from July 2009 to June 2010. For this, 60 pregnant women of preeclampsia, age ranged from 18 to 39 years, more than 20th weeks of pregnancy were included in the study (group B). They were further divided into group B1 consisting of 30 mild preeclamptic women and group B2 consisting of 30 severe preeclamptic women. For comparison age and gestational period matched 30 normotensive pregnant women control (group A) were also studied. Both control (group A) and preeclamptic women were selected from Obstetric and Gynae in and out patient Department of BSMMU and Dhaka Medical College Hospital. Maternal hemoglobin concentration was measured by standard laboratory techniques. Result: In this study, hemoglobin levels were significantly higher in study (group B) than those of control (group A). Again Hemoglobin levels were higher in group B2 than B1, but not significant (P>0.05). Hemoglobin level was positively correlated with systolic and diastolic blood pressure but it was statistically non-significant (P>0.05). Conclusion: The study concluded that serum hemoglobin level is associated with preeclampsia. Journal of Current and Advance Medical Research, January 2021;8(1):39-43]